Quantum computers - an emerging cybersecurity threat - Jelčić Dubček, Dajana (Array, 2021)
Quantum computational supremacy may potentially endanger the current cryptographic protection methods. Although quantum computers are still far from a practical implementation in information processing and storage, they should not be overlooked in the context of cybersecurity. Quantum computers operate with qubits - units of information that are governed by the fundamental principles of quantum physics, such as quantum superposition of states and quantum coherence. In order to address the new challenge that quantum computers pose to cybersecurity, the very principles of their operation have to be understood and are overviewed in this contribution.